Changes in golf course fairway soils under effluent water irrigation - Skiles, David John, author; Qian, Yaling, advisor; Andales, Allan A., committee member; Koski, Tony, committee member (Colorado State University. Libraries, 2010)
As the use of effluent irrigation increases, salinity and sodicity issues associated with its use continue to be of great concern to the golf course industry. The purpose of our research was to (i) observe salinity accumulation patterns on 4 fairways of two effluent water irrigated golf courses using 2 different types of sensors and to (ii) determine long-term changes in soil chemistry in soils under effluent water irrigation on golf course fairways. Temporal and spatial accumulation patterns were measured using a network of in-situ soil sensors located at two depths 15 and 30 cm for 5TE sensors and 8 and 19cm for Turf Guard sensors (TG2). Sensors measured electrical conductivity (EC), volumetric soil water content (SWC), and soil temperature data were collected continuously during the 2008 and 2009 growing seasons. Correlation was observed between 5TE sensor-measured soil salinity vs. saturated paste extracted soil salinity (r = 0.77). A significant exponential relationship was observed between TG2 sensor-measured soil salinity vs. saturated paste extracted soil salinity (R² = 0.97). In-ground measurements indicated that salinity can vary widely across a seemingly homogenous golf course fairway in a manner reflective of the underlying soil physical characteristics. Plots exhibiting low and high salinities presented opposite seasonal trends at Heritage Golf Course. Strong correlation was observed between average soil salinity and mean soil water content (r =0.76), soil salinity and the percentage of sand in the soil texture composition (r = -0.63) for Heritage fairway 1. High salinity was found on fairway 19 at Common Ground Golf Course. However, the salinity level as high as 10.6 dS/m is not a result of water reuse, but a historical geological contribution. Drainage appears to be vital in maintaining low soil salinity levels under effluent irrigation in clay soils. Slow to infiltrate, percolate and difficult to leach; predominately clay soils irrigated with effluent water can accumulate soil salinity over time. Our data suggested that a robust drainage network in predominantly clay soils irrigated with effluent could better manage salinity accumulation associated with poor drainage. To determine long-term changes in soil chemistry in soils under effluent water irrigation on golf course fairways, soil testing data was provided by the superintendent for the years of 1999, 2000, 2002, 2003, and 2009 for Heritage Golf Course in Westminster, Colorado. Soil samples were tested by Brookside Laboratories, Inc, New Knoxville, OH. Parameters of each soil sample tested included pH, extractable salt content (calcium, magnesium, potassium, sodium, iron, manganese, copper, zinc, phosphorus, and boron), base saturation percent of calcium, magnesium, potassium and sodium, soil organic matter (SOM), and cation exchange capacity (CEC). Regression analysis was used to evaluate the changes in individual soil parameters over time after the use of effluent water for irrigation. Soil pH, CEC, extractable aluminum, copper, manganese and iron along with both base saturation percentages and exchangeable percentages of calcium and magnesium did not change over time. The strongest indications of change are seen for extractable boron (R² = 0.56), Bray II extracted phosphate (R² = 0.56), and sodium base saturation percentage (R² = 0.44). The regression analysis indicated that B, P, and sodium increased linearly during the 8 year's irrigation with effluent water. Further studies are needed to determine if these parameters would continue to increase or would stabilize. Continued accumulation of sodium could eventually result in loss of soil structure.